A pragmatic, clinically optimized approach to characterizing adolescent irritability: Validation of parent‐ and adolescent reports on the Multidimensional Assessment Profile Scales—Temper Loss Scale - Nathan Kirk; Emily Hirsch; Tasmia Alam; Lauren S. Wakschlag; Jillian Lee Wiggins; Amy K. Roy (International Journal of Methods in Psychiatric Research, 2023)
Abstract Objectives Heightened irritability in adolescence is an impairing symptom that can lead to negative outcomes in adulthood, but effective screening tools are lacking. This study aimed to derive clinically‐optimized cutoff scores using the Multidimensional Assessment Profile Scales–Temper Loss (MAPS‐TL) to pragmatically identify adolescents with impairing irritability. Methods A diverse sample of 79 adolescents and their parents completed the MAPS‐TL‐Youth version. Stepwise logistic regression analyses were used to determine the items associated with impairment, and receiver operator characteristic (ROC) analyses were conducted to derive optimal cutoff scores. Results Three parent‐report items (become frustrated easily, angry/irritable/grouchy throughout the day, difficulty calming down when angry) and two youth‐report items (hit/shove/kick when lost temper, difficulty calming down when angry) were strongly associated with impairment. Optimal cutoff scores garnered very good sensitivity (91%, 73%) and specificity (77%, 75%) for the parent‐ and youth‐report versions respectively. Scores above these cutoffs were associated with increased internalizing and externalizing problems and lower overall quality of life. Conclusions The MAPS‐TL clinically optimized irritability scores show preliminary validity for implementation in practical settings to efficiently identify adolescents who need additional evaluation and/or intervention. Further research is important to validate these cutoff scores with larger population‐based samples and real‐world settings.